The conceptions of public healthcare nurses about care - Sonia Silva Marcon; Keli Regiane Tomeleri; Betina Barbedo Andrade; Lilian Denise Mai; Marta Elaine Serafim Santos (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The art of caring is arousing the conscience of being a nurse to a redirection of his/her role as a caring being who becomes involved with other beings. This study aims to identify the understanding that nurses have about caretaking and its practical applicability according to the theorists Leonardo Boff and Vera Regina Waldow. A descriptive and qualitative study, carried out with nurses from Basic Healthcare Units, where 94.1% are women, 58.8% are between 41-50 years old, the majority (76.5%) of them are specialists and 52.9% graduated in the 1980s. This situation produced three categories: the Assistance category - "do something for somebody", the Feeling category - "care with humanistic values", and the Education category - "promotion of the quality of life". It was observed that that nurses spoke mainly in terms of "doing to" or "doing for" someone, rather than "doing with" someone. A great difficulty and certain confusion were observed, when speaking about care.